The role of international organizations in the design of public development policies - Rodríguez Hernández, Edgar Ricardo (Cooperativismo & Desarrollo, 2019)
his article aims to theoretically and empirically examine the role of international organizations in the designof public development policies under a context of asymmetric power relations between state and non-stateactors. In this sense, it has been identified that the determining factors that influence the role of international organizations in forming coalitions with state and non-state actors in the design of development policies are the power structure and trust. A series of strategies are presented with which an international organization, regardless of specialization, could improve such aspects, among which are: change in the ideological discourse of development, decrease in the autonomy of groups with power or the elite within public politics, promotion of institutional transparency, accountability and post-development support monitoring.
Keywords: body; development policies; state actors; non-state actors